Pembinaan Dan Penguatan Karakter Generasi Muda Melalui Sinergi Building Dan Entrepreneurship Programme Desa Glagah Lamongan. - Maulidyah Amalina Rizqi (Jurnal Pengabdian Manajemen, 2021)
As a young generation, they must have the provision of creativity, innovation, intelligence and skills that can benefit the environment around them. As a young generation with character, they must be able to have a strong mentality in dealing with various problems that occur in society. Character alone is not enough for the younger generation, but must be able to think creatively and innovatively through entrepreneurship programs. Because at this time the field in the world of work has begun to fill up, the younger generation does not have to look for work but they should be the ones who create jobs. So coaching the younger generation for entrepreneurship programs is also necessary and important to be given to the younger generation. The material presented by the implementing team of this Community Service program will initiate partners to become entrepreneurs with character, so there are several scientific fields that will be given, namely entrepreneurship, managerial science (POAC), production processes to sales processes, leadership, organizational science , craft science, arts, synergy building and cultivation science to be able to provide input or ideas to partners regarding what business fields they can do later.